2006
DOI: 10.1136/bjo.2005.078212
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of combined phacoemulsification and trabeculectomy with releasable sutures

Abstract: Aim: To evaluate the combined phacoemulsification with acrylic intraocular lens implantation and trabeculectomy with releasable sutures, without the use of antimetabolites, performed by one surgeon. Methods: A retrospective analysis was performed on 251 eyes of 198 patients after a combined phaco/trabeculectomy procedure, followed up for an average of 16 months for vision, intraocular pressure (IOP), and number of glaucoma medications. Cox proportional hazard regression analysis provided measures of relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
1
12
0
4
Order By: Relevance
“…Jongsareejit et al 6 report that only about 40% of Japanese patients with NTG successfully maintained an IOP level 20% lower than the preoperative IOP after trabeculectomy with MMC. Stark et al 41 report that they performed phacotrabeculectomy without antimetabolite agents in white glaucoma patients with low IOP (mean 18.7 mm Hg); the final mean reduction was 19.2%. These results are comparable to ours.…”
Section: Discussionmentioning
confidence: 96%
“…Jongsareejit et al 6 report that only about 40% of Japanese patients with NTG successfully maintained an IOP level 20% lower than the preoperative IOP after trabeculectomy with MMC. Stark et al 41 report that they performed phacotrabeculectomy without antimetabolite agents in white glaucoma patients with low IOP (mean 18.7 mm Hg); the final mean reduction was 19.2%. These results are comparable to ours.…”
Section: Discussionmentioning
confidence: 96%
“…3,6 Stark et al 19 found mean IOP reduction of 19.2% in a retrospective analysis of phacotrabeculectomy without antimetabolites. It is likely that greater percentage reduction in IOP were achieved owing to higher preoperative IOP levels, which must be kept in mind while comparing different studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 The overall success achieved (IOPr18 mm Hg) without or with medication was 490% when combined with either MSICS (90.6%) or phacoemulsification (95.4%), which was better than combined surgery results on Indian eyes. 3,19 We also analyzed the success taking IOPr15 and r12 mm Hg in both types of surgeries. The success reported was 70 and 51% with MSICS and 73 and 50% with phacoemulsification, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 13 20 Without MMC, Stark et al achieved a 78% medication-free rate over a period of 42 months in a primarily white population. 9 We achieved a medication-free rate of 61% at the final consultation, and the average patient decreased 1.0 ± 1.3 medications. Our patients were predominantly of West Indian race and we found that with MMC application many patients were able to achieve target pressures without medication.…”
Section: Discussionmentioning
confidence: 76%
“… 7 However, several authors have recently achieved comparable success rates with single surgical sites and without MMC. 9 - 11 Patients with risks for filtration failure, such as black race, diabetes mellitus, and use of more than two preoperative glaucoma medications, are often recommended simultaneous MMC to prevent failure and glaucoma progression. 12 However, its use is associated with increased bleb leaks and the long-term risk of blepharitis, endophthalmitis, and hypotony.…”
Section: Introductionmentioning
confidence: 99%